Flexible Application-Layer Multicast in Heterogeneous Networks - Hübsch, Christian (KIT Scientific Publishing, 2013)
This work develops a set of peer-to-peer-based protocols and extensions in order to provide Internet-wide group communication. The focus is put to the question how different access technologies can be integrated in order to face the growing traffic load problem. Thereby, protocols are developed that allow autonomous adaptation to the current network situation on the one hand and the integration of WiFi domains where applicable on the other hand.